High-voltage engineering - Kuffel, E (Applied electricity and electronics division., 1970)
Power transfer for large systems depends on high system voltages. The basics of high voltage laboratory techniques and phenomena, together with the principles governing the design of high voltage insulation, are covered in this book for students, utility engineers, designers and operators of high voltage equipment.